Neutronics Perturbation Calculation Method Study of Solid Breeder Tritium Breeding Blanket for TBR Enhancement - Qu, Shen; Cao, Qixiang; Zhao, Fengchao; Wang, Xueren; Duan, Xuru; Wang, Xiaoyu (Frontiers in Energy Research, 2021)
Tritium breeding blanket (TBB) is an essential component in a fusion reactor, which has functions of tritium breeding, energy generation, and neutron shielding. Tritium breeding ratio (TBR) is a key parameter to evaluate whether the TBB could produce enough tritium to achieve the tritium self-sufficiency (TBR >1) for fusion reactor. Current codes or software are hard to meet the requirements of high efficiency, high resolution, and high automation for neutronic optimization of TBB. In this article, the application of the density perturbation calculation on a solid breeder TBB was first performed. Then, the method of the geometry perturbation calculation based on the virtual density theory was studied. Results and comparison analysis indicate that the 1st + 2nd-order neutronic perturbation calculations (including the density perturbation and the geometry perturbation) results are consistent with the transport results under a perturbation of −15% to +15%. It is proven to be valid to use the perturbation calculation for rapid TBR enhancement study of the solid breeder TBB.